2000
DOI: 10.1177/074873040001500608
|View full text |Cite
|
Sign up to set email alerts
|

The Coincidence of Light and Melatonin with a Specific Phase of the Circadian Pacemaker Is Important for the Timing of Seasonal Breeding in the Ewe

Abstract: The timing of reproductive activity in seasonal breeding sheep relies on daily photoperiodic signals being relayed to provide information on the time of year. Although light and melatonin are involved, the exact mechanism is not understood. In this experiment, three groups of 6 Romney Marsh ewes, a highly seasonal breed, were provided with 8 weeks of short nights (9.6-9.8 h, by artificially advancing dawn) around the winter solstice, near the end of their natural breeding season. One group of animals was infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 23 publications
1
4
0
4
Order By: Relevance
“…No seasonal differences were observed in blood samples collected before (17:00 hr) or after (8:00 hr) the annual dusk and dawn times respectively (Table 3). These results are in agreement with those existing in the literature, which have demonstrated that all seasonal changes, which characterize the classic annual pattern of plasma melatonin concentration, occur during the nocturnal times [26,27,29,30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No seasonal differences were observed in blood samples collected before (17:00 hr) or after (8:00 hr) the annual dusk and dawn times respectively (Table 3). These results are in agreement with those existing in the literature, which have demonstrated that all seasonal changes, which characterize the classic annual pattern of plasma melatonin concentration, occur during the nocturnal times [26,27,29,30].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, it was not possible to determine exactly the rise times of elevated melatonin, but it could be inferred that the rise times of elevated melatonin were at or after dusk when seasonal differences were evidenced. In fact, the onset of melatonin is clearly delayed relative to dusk at all times of year as ewes were kept under natural or artificial photoperiod at 35°S in Australia and this delay was significantly greater in winter [26,30,31]. Although the difference in winter night (13.3 hr) and summer night (10.7 hr) at the latitude of the present study is only 2.6 hr, the model of annual melatonin secretion of wool and hair sheep seems to be the same of those raised under natural or artificial conditions in intermediate or high latitudes in southern or northern hemispheres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two main alternative hypotheses have been proposed to explain how nycthemeral melatonin secretion controls reproductive activity: the duration of the melatonin secretion, and the temporal phase of this rise relative to the light-dark cycle have both been considered [7][8][9][10]. For each hypothesis, the amplitude of melatonin secretion may play a specific role to modulate the response; it has been suggested that the ratio nocturnal/diurnal melatonin after implant insertion [11] or under natural conditions [12] could be related to the speed of resumption of ovulatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…The hormone melatonin is synthesized and secreted foremost by the mammalian pineal gland following a distinct circadian rhythm with the acrophase during the dark phase, and the nadir during the light phase in both diurnal and nocturnal species [1]. Melatonin modulates a number of physiological, behavioral and neuroendocrine functions in mammals including sleep promotion [2], phase shift and entrainment of circadian rhythms [3–5], and reproduction in seasonal breeders [6, 7]. There is growing evidence suggesting a role for melatonin in the pathophysiology of affective disorders, namely, depression.…”
Section: Introductionmentioning
confidence: 99%